Differences in Academic Achievement as a Function of Instructional Expenditure Ratio for Students in Poverty - Susan Hoisington; John R. Slate; Cynthia Martinez-Garcia; Cynthia Martinez-Garcia (Athens Institute for Education and Research, 2018)
In this investigation, the effect of instructional expenditure ratio grouping on the Texas Assessment of Knowledge & Skills Reading, Mathematics, Science, Social Studies, and Writing test passing rates for students in poverty was examined. Data were obtained from the Texas Education Agency on all Texas high school students for the 2006-2007 through the 2010-2011 school years. In all analyses, statistically significant differences, with small to moderate effect sizes, were present in passing rates as a function of instructional expenditure ratio grouping for students in poverty. School districts that had an instructional expenditure of at least 60% had higher TAKS passing rates in all five academic areas for students in poverty than school districts that spent less than 60% on instruction. Suggestions for future research and implications for policy and practice were made.